Binuclear Metal Complexes of Cobalt (II) with the ligand 1,2,5,6-Tetraphenyl-3,4-Diaza-1,6-Dihydroxymino-2,4-Hexadiene - Sahu, K.; Mahto, Kailash; Chandra Yadav, Shiv (Asian Journal of Chemistry, 2010)
Binuclear metal complexes of Co(II) with the ligand 1,2,5,6- tetraphenyl-3,4-diaza-1,6-dihydroxyimino-2,4-hexadiene of the type Co2L2X4 (X = Cl-, Br-, I- or NO3- have been prepared and characterized on the basis of analytical, IR, electronic and magnetic moment data. IR spectral data show coordination of the ligand with the metal ions through the azine and oxime nitrogens in a bi-bidentate manner. The complexes are suggested to possess a hydrogen bonded binuclear structure on the basis of IR data. Magnetic values and electronic spectra show a tetragonal crystal field around metal ions.